Characterization of fluorescence in heat-treated silver-exchanged zeolites - De Cremer, Gert; Coutiño-Gonzalez, Eduardo; Roeffaers, Maarten B J; Moens, Bart; Ollevier, Jeroen; Van der Auweraer, Mark; Schoonheydt, Robert; Jacobs, Pierre A; De Schryver, Frans C; Hofkens, Johan; De Vos, Dirk E; Sels, Bert F; et al. (Journal of the American Chemical Society, 2009)
Thermal treatment of Ag(+)-exchanged zeolites yields discrete highly photostable luminescent clusters without formation of metallic nanoparticles. Different types of emitters with characteristic luminescence colors are observed, depending on the nature of the cocation, the amount of exchanged silver, and the host topology. The dominant emission bands in LTA samples are situated around 550 and 690 nm for the samples with, respectively, low and high silver content, while in FAU-type materials only a broad band around 550 nm is observed, regardless of the degree of exchange. Analysis of the fluorescent properties in combination with ESR spectroscopy suggests that a Ag(6)(+) cluster with doublet electronic ground state is associated with the appearance of the 690-nm emitter, having a decay of a few hundred microseconds. Tentatively, the nanosecond-decaying 550-nm emitter is assigned to the Ag(3)(+) cluster. This new class of photostable luminescent particles with tunable emission colors offers interesting perspectives for various applications such as biocompatible labels for intracellular imaging.